2017
DOI: 10.3389/fcimb.2017.00230
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Virulence Profile of Enteroaggregative Escherichia coli Strains Isolated from Danish Children with Either Acute or Persistent Diarrhea

Abstract: Enteroaggregative Escherichia coli (EAEC) is frequently found in diarrheal stools worldwide. It has been associated with persistent diarrhea, weight loss, and failure to thrive in children living in developing countries. A number of important EAEC virulence genes are identified; however, their roles in acute and persistent diarrhea have not been previously investigated. The aim of this study was to identify specific EAEC virulence genes associated with duration and type of diarrhea in Danish children. We aimed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 71 publications
1
22
0
1
Order By: Relevance
“…We detected high levels of antibiotic resistance among 137 EAEC strains isolated from Danish adults suffering from diarrhea. Previously, we have detected MDR among 35% of EAEC strains in Danish children in daycare (Hebbelstrup Jensen et al, 2016 ), and in 38% of EAEC strains isolated from Danish children with diarrhea (Hebbelstrup Jensen et al, 2017 ). Surprisingly, in this study, we detected a high level of resistance toward ciprofloxacin (34%), which is still one of the most frequently used antimicrobials for diarrhea (Kong et al, 2015 ).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…We detected high levels of antibiotic resistance among 137 EAEC strains isolated from Danish adults suffering from diarrhea. Previously, we have detected MDR among 35% of EAEC strains in Danish children in daycare (Hebbelstrup Jensen et al, 2016 ), and in 38% of EAEC strains isolated from Danish children with diarrhea (Hebbelstrup Jensen et al, 2017 ). Surprisingly, in this study, we detected a high level of resistance toward ciprofloxacin (34%), which is still one of the most frequently used antimicrobials for diarrhea (Kong et al, 2015 ).…”
Section: Discussionmentioning
confidence: 85%
“…The astA gene encodes the enterotoxin EAST-1, which is commonly detected in EAEC strains, and has previously been associated with watery diarrhea (Ménard and Daniel Dubreuil, 2002 ; Kaper et al, 2004 ). Previously, we have described how the astA is important in prolonged diarrhea in children (Hebbelstrup Jensen et al, 2017 ). However, many commensal E. coli strains also harbor the EAST-1 toxin, and it has, therefore, been suggested that additional virulence factors are required to mediate diarrhea (Konno et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…The aatA gene is a key gene in enteroaggregative E. coli (EAEC) and it encodes part of the outer membrane transport system (ABC transporter) involved in the translocation of the dispersin protein. The aatA and astA genes are associated with prolonged diarrhea in EAEC strains [21]. Three different phylogenetic groups were detected, although all isolates came from the same farm.…”
Section: Resultsmentioning
confidence: 98%
“…2). Notably, nine phylogenetically diverse E. coli (median, 37,617 SNPs), including three soil isolates (HH25S, HH26S, and HH51S), coharbored aatA and astA (the simultaneous presence of aatA and astA has been associated with prolonged diarrhea [47]), highlighting the diversity of pathogenic E. coli circulating in these rural Bangladeshi communities. The presence of astA in the absence of additional pathogenic markers, as observed in eight E. coli isolates, lacks the discriminatory power to assign these strains within any of the intestinal pathotypes, as astA has been associated with multiple intestinal pathotypes (48)(49)(50) and is also prevalent in extraintestinal (51), commensal (50), and environmental isolates (52).…”
Section: Discussionmentioning
confidence: 99%